Removal of seed of Grevillea pteridifolia by ants - Majer, Jonathan; Lamont, B. B. (1985)
Seed-taking by ants has rarely been recorded in Australian Proteaceae. Recent work in northern Australia showed that seed of Grevillea pteridifolia is taken by ants as readily as those of certain elaiosome-bearing Acacia spp. The hard, flat seed is completely surrounded by a brittle, papery wing which is consumed by ants. The wing contributes 3-5% of seed mass and has a higher concentration of protein, available carbohydrate, fat and certain micronutrients than the seed body (embryo + coat). Although present throughout the seed, cyanide is concentrated in the seed coat. The high lipid and protein content of the wing explains its success as an ant attractant while the hard, cyanide-containing seed coat may deter seed predation. The apparent absence of seed taking by ants in closely related proteaceous genera in Australia may be attributed to serotiny as the general condition, while Grevillea spp. release seed annually and should benefit from the storing of seed in soil by ants.